Japanese Imperialism: Politics and Sport in East Asia Rejection, Resentment, Revanchism (Springer Singapore, 2018)
This cutting edge collection presents a political reading of the power of modern sport in Asia. Providing an interdisciplinary study of political and cultural tensions in Asia, past and present, through the key case-study of sport, it illuminates the complex practices and legacies of Japanese imperialism across East and Southeast Asia through the 20th century and beyond. Focusing on the deep background to contemporary dynamics of intraregional tensions, it examines sport both as a tool of imperialism and as an agent of reconciliation as the region gears up to the 2020 Olympics in Tokyo. Offering a unique contribution to East Asian Studies, Colonial and Postcolonial Studies and Sport Studies, this work represent key reading for students and scholars of East Asian studies, International Politics and Sports Diplomacy. .